2008
DOI: 10.1021/cm802483w
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Structural Study of Glassy and Metastable Crystalline BaTi2O5

Abstract: The structures of glassy and metastable crystalline BaTi 2 O 5 fabricated by the containerless method were comprehensively investigated by combined X-ray and neutron diffractions, XANES analyses, and computer simulations. The three-dimensional atomic structure of glassy BaTi 2 O 5 (g-BaTi 2 O 5 ), simulated by Reverse Monte Carlo (RMC) modeling on diffraction data, shows that extremely distorted TiO 5 polyhedra interconnected with both corner-and edge-shared oxygen formed a higher packing density structure tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 27 publications
5
67
0
Order By: Relevance
“…Barium aluminotitanate glasses are of interest due to physical properties that lend them to potential applications, for example, in the encapsulation of radionucleides in highly active nuclear waste [1][2][3][4], high refractive index materials for use in high-capacity optical disk storage systems [5], broadband photoluminescent materials [6], and as precursors for glass-ceramics for optical [7] and ferroelectric [8] applications. Further applications may arise from the ability to control the local nucleation and growth of crystals to form patterned glass ceramics by systematic annealing of the glass through, for example, laser treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Barium aluminotitanate glasses are of interest due to physical properties that lend them to potential applications, for example, in the encapsulation of radionucleides in highly active nuclear waste [1][2][3][4], high refractive index materials for use in high-capacity optical disk storage systems [5], broadband photoluminescent materials [6], and as precursors for glass-ceramics for optical [7] and ferroelectric [8] applications. Further applications may arise from the ability to control the local nucleation and growth of crystals to form patterned glass ceramics by systematic annealing of the glass through, for example, laser treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The use of laser heating and containerless aerodynamic levitation enables three component rare-earth gallate glasses to be made, thus simplifying an interpretation of the neutron diffraction results. This preparation method also allows for the possibility of making glasses with novel opto-electronic and magneto-optical properties [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Yu et al successfully vitrified BaTi 2 O 5 without adding any network-forming oxides using containerless processing with an aerodynamic levitation (ADL) furnace [7]. The structural analysis using X-ray and neutron diffraction measurements and computational modeling with a reverse Monte Carlo method suggested that distorted Ti-O polyhedra, with an average coordination number of approximately 5, were present in the glass and formed a highly dense glass structure [8]. Recently, we demonstrated that a BaTi 2 O 5 glass had excellent optical properties, such as a refractive index exceeding 2.1, colorlessness, and transparency in the visible region [9,10].…”
Section: Introductionmentioning
confidence: 99%